Basic MOSFET Based vs Couple-Coils Boost Converters for Photovoltaic Generators - Pierre Petit; Michel Aillerie; The Vinh Nguyen; Jean-Pierre Charles (Institute of Advanced Engineering and Science, 2014)
Considering the optimization of a photovoltaic system, several studies show the advantage in the choice of a distributed structure. For such structures small power converters such as the boosts and buck converters appear as most appropriate. We have analysed the efficiency of small power boost-converters especially dedicated for photovoltaic energy conversion systems working in the middle and high voltage ranges. The setup studied is a photovoltaic generator connected to an AC grid working in 230 Volts via an inverter. More over, we considered the possibility of multiple electrical energy sources as photovoltaic, wind systems in the same energy production system, which obliged an adaptive converter structure. We evaluated the losses in the various stages of a boost converter and point out the importance of the power MOSFET used as the commutation element. New transistors databases obtained from manufacturers show the nonlinear dependency between the resistance drain-source when passing, Rdson and the maximum rating voltage when the transistor is off, Vdsmax, for all transistor families. Thus nonlinear dependency induces a huge increase of losses with the voltage in the MOSFET, and as a direct consequence in the converter the more as Vdsmax is higher. In order to minimize losses of the converter we have designed and realized a new high efficiency version of a Step-Up structure based on a commutation element integrating a low Vdsmax voltage MOSFET and very low Rdson.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4484